Different Selected Mechanisms Attenuated the Inhibitory Interaction of KIR2DL1 with C2(+) HLA-C in Two Indigenous Human Populations in Southern Africa - Nemat-Gorgani, Neda (AMER ASSOC IMMUNOLOGISTS, 2021)
10.4049/jimmunol.1701780